Reconstruction of the Authority of the Papuan People's Assembly Based on the Principles of Siyasah Syar'iyyah: A Study of the Function of Cultural Representation - Lukman Ansar; Sabar Podu; Lisma; Satriadi; Zulfadli; Dandi Wahyudin; Andi Miftahul Maulidil Mursyid (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This article examines the structural limitation of authority exercised by the Papuan People’s Assembly (Majelis Rakyat Papua -MRP), a cultural representative institution established under Indonesia’s Special Autonomy framework. Despite its strong moral and cultural legitimacy to protect the identity and fundamental rights of Indigenous Papuans, MRP’s authority remains largely procedural, creating a persistent gap between its normative mandate and practical influence in regional governance. Existing studies tend to frame this limitation as an administrative or political issue, leaving its normative and theoretical dimensions underexplored. This study offers a conceptual reconstruction of MRP’s authority through the lens of Siyasah Syar’iyyah, employed as a normative governance framework rather than a merely ethical reference. Using a normative juridical method that integrates conceptual, statutory, and historical approaches, the research develops a prescriptive model grounded in the principles of al-maslahah (public welfare), al-‘adl (justice), and hifz al-‘ird (protection of dignity). The findings demonstrate that this framework enables a redefinition of MRP from a symbolic cultural body into a substantive guardian of Indigenous interests with strengthened consultative authority possessing normative effects. The article contributes by bridging Islamic political jurisprudence and indigenous governance, while offering a normative-institutional basis for enhancing cultural justice within Papua’s Special Autonomy system.